# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime } = \frac {y}{y-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{y-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{y-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{y-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x y}{x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x y}{x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x y}{x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \sqrt {1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \sqrt {1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \sqrt {1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \sqrt {1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {x}{2}+\frac {\sqrt {x^{2}+4 y}}{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {x}{2}+\frac {\sqrt {x^{2}+4 y}}{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {x}{2}+\frac {\sqrt {x^{2}+4 y}}{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {x}{2}+\frac {\sqrt {x^{2}+4 y}}{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {x}{2}+\frac {\sqrt {x^{2}+4 y}}{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-i y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 4
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = 2 \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 y = 6
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = \left \{\begin {array}{cc} 2 & 0\le x <1 \\ 1 & 1\le x \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 y = \delta \left (x -2\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-3 y = \delta \left (x -1\right )+2 \operatorname {Heaviside}\left (x -2\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y+1}{t +1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t^{2} y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t^{4} y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 y+1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2-y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{-y}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = 1+x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 t y^{2}+3 y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {t}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {t}{t^{2} y+y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t y^{{1}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{2 y+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 y+1}{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \left (1-y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {4 t}{1+3 y^{2}}
\] |
✓ |
✓ |
|
\[
{}v^{\prime } = t^{2} v-2-2 v+t^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{t y+t +y+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {{\mathrm e}^{t} y}{1+y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-4
\] |
✓ |
✓ |
|
\[
{}w^{\prime } = \frac {w}{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sec \left (y\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = -t x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t^{2} y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {t}{y-t^{2} y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 y+1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t y^{2}+2 y^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = \frac {t^{2}}{x+t^{3} x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1-y^{2}}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (1+y^{2}\right ) t
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{2 y+3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 t y^{2}+3 t^{2} y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{2}+5}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t^{2}+t
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t^{2}+1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1-2 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4 y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 y \left (1-y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y+t +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 y \left (1-y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 y-t
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (y+\frac {1}{2}\right ) \left (y+t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (t +1\right ) y
\] |
✓ |
✓ |
|
\[
{}S^{\prime } = S^{3}-2 S^{2}+S
\] |
✗ |
✓ |
|
\[
{}S^{\prime } = S^{3}-2 S^{2}+S
\] |
✗ |
✓ |
|
\[
{}S^{\prime } = S^{3}-2 S^{2}+S
\] |
✓ |
✓ |
|
\[
{}S^{\prime } = S^{3}-2 S^{2}+S
\] |
✓ |
✓ |
|
\[
{}S^{\prime } = S^{3}-2 S^{2}+S
\] |
✗ |
✓ |
|
\[
{}y^{\prime } = y^{2}+y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{3}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -t^{2}+2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t y+t y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t^{2}+t^{2} y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t +t y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t^{2}-2
\] |
✓ |
✓ |
|
\[
{}\theta ^{\prime } = \frac {9}{10}-\frac {11 \cos \left (\theta \right )}{10}
\] |
✓ |
✓ |
|
\[
{}\theta ^{\prime } = 2
\] |
✓ |
✓ |
|
\[
{}\theta ^{\prime } = \frac {11}{10}-\frac {9 \cos \left (\theta \right )}{10}
\] |
✓ |
✓ |
|
\[
{}v^{\prime } = -\frac {v}{R C}
\] |
✓ |
✓ |
|
\[
{}v^{\prime } = \frac {K -v}{R C}
\] |
✓ |
✓ |
|
\[
{}v^{\prime } = 2 V \left (t \right )-2 v
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 y+1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t -y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-4 t
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (y\right )
\] |
✓ |
✓ |
|
\[
{}w^{\prime } = \left (3-w\right ) \left (w+1\right )
\] |
✓ |
✓ |
|
\[
{}w^{\prime } = \left (3-w\right ) \left (w+1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{\frac {2}{y}}
\] |
✗ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{\frac {2}{y}}
\] |
✗ |
✓ |
|
\[
{}y^{\prime } = y^{2}-y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 y^{3}+t^{2}
\] |
✗ |
✗ |
|